2005
DOI: 10.1093/ndt/gfh924
|View full text |Cite
|
Sign up to set email alerts
|

The calcimimetic cinacalcet normalizes serum calcium in renal transplant patients with persistent hyperparathyroidism

Abstract: Calcimimetics are a promising therapy in renal transplant patients with persistent hyperparathyroidism. Prospective controlled studies must now be designed focusing on functionally relevant musculo-skeletal end-points and allowing the exclusion of negative effects on long-term renal and general outcome of such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
1
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(107 citation statements)
references
References 18 publications
5
93
1
8
Order By: Relevance
“…Calcimimetics inhibit PTH secretion by modulating the calcium-sensing receptor in the parathyroid gland and could represent an alternative approach in these patients. In a recent study, 30 mg/d cinacalcet for 3 mo normalized the serum calcium in all but two patients, whereas serum PTH and phosphate levels did not change significantly (80). Similarly, Serra et al (81) showed in a short study of 10 wk duration that cinacalcet was effective in correcting the hypercalcemia and reducing PTH values in patients who received a transplant and had persistent hyperparathyroidism.…”
Section: Role Of Calcimimeticsmentioning
confidence: 84%
“…Calcimimetics inhibit PTH secretion by modulating the calcium-sensing receptor in the parathyroid gland and could represent an alternative approach in these patients. In a recent study, 30 mg/d cinacalcet for 3 mo normalized the serum calcium in all but two patients, whereas serum PTH and phosphate levels did not change significantly (80). Similarly, Serra et al (81) showed in a short study of 10 wk duration that cinacalcet was effective in correcting the hypercalcemia and reducing PTH values in patients who received a transplant and had persistent hyperparathyroidism.…”
Section: Role Of Calcimimeticsmentioning
confidence: 84%
“…More recently, cinacalcet has been used in KTx recipients (5,6). Kruse et al (5) reported successful reduction in SCa levels in 14 KTx recipients with persistent HPT after TX. They did not see, however, a statistically significant decrease in PTH levels (5).…”
Section: Discussionmentioning
confidence: 99%
“…We report herein our experience with cinacalcet in the management of persistent HPT and hypercalcemia after KTx. We also compare and contrast our experience with the recently published experience of two other groups that have used cinacalcet in a similar manner (5,6).…”
mentioning
confidence: 95%
“…Cinacalcet (Sensipar 1 / Mimpara 1 ; Amgen Inc., Thousand Oaks, CA), an allosteric modulator of the CaSR, has demonstrated efficacy in decreasing calcium and PTH in patients with secondary HPT on dialysis (21); and in a number of small, open-label, single arm, single-center and retrospective studies, cinacalcet decreased serum calcium and PTH and increased serum phosphorus levels in renal transplant recipients with persistent HPT (22)(23)(24)(25)(26)(27)(28). In these studies, cinacalcet was well tolerated with no evidence of adverse effects on immunosuppressive therapy or allograft function.…”
Section: Introductionmentioning
confidence: 99%